Integrative analysis of WDR12 as a potential prognostic and immunological biomarker in multiple human tumors - Eid, Refaat A.; Eldeen, Muhammad Alaa; Soltan, Mohamed A.; Al-Shraim, Mubarak; Aldehri, Majed; Alqahtani, Leena S.; Alsharif, Ghadi; Albogami, Sarah; Jafri, Ibrahim; Fayad, Eman; Park, Moon Nyeo; Bibi, Shabana; et al. (Frontiers in Genetics, 2023)
Mammalian WD-repeat protein 12 (WDR12), a family member of proteins containing tryptophan–aspartic acid (WD) repeats, is a potential homolog of yeast Ytm1p and consists of seven WD repeats. WDR12 is a candidate for functioning as an oncogene in various human malignancies. Despite this, there is not yet a pan-cancer analysis that has been carried out to investigate the various patterns in which this gene is expressed and behaves in tumor tissues. In the current study, we used Gene Cancer Genome Atlas (TCGA) and various computational tools to explore expression profiles, prognostic relevance, genetic mutations, immune cell infiltration, as well as the functional characteristics of WDR12 in multiple human cancers. Herein, we found that WDR12 was inconsistently expressed in various cancers, and variations in WDR12 expression predicted survival consequences for cancer patients. Furthermore, we observed a significant correlation between WDR12 gene mutation levels and the prognosis of some tumors. In addition, significant correlations were found between WDR12 expression patterns and the infiltration of cancer-associated fibroblasts (CAFs), myeloid-derived suppressor cells (MDSCs), tumor mutation burden, microsatellite instability, and immunoregulators. Ultimately, pathway enrichment analysis revealed that WDR12-related pathways are involved in carcinogenesis. In conclusion, we have obtained satisfactory results demonstrating that WDR12 could serve as a promising and reliable prognostic biomarker, as well as a therapeutic target for novel cancer therapeutic approaches. Keywords: WDR12; pan-cancer; prognosis; immunotherapy.